What is a good “serious game” like? Game development, testing, and student feedback - Kéri, Anita; Prónay, Szabolcs (Vezetéstudomány / Budapest Management Review, 2022)
Gamification has been at the centre of research interest in different fields. It has been widely used in pedagogy, medical sciences, and business studies. A key methodology of gamification is serious games. Although these games are available for higher education institutions, they are costly, and the content of the game cannot be customised for specific classrooms. The aim of this study is to test a newly developed serious game that is freely accessible online and whose content can be customised. Measuring student satisfaction and experience, testing the game, and collecting feedback from students provide an opportunity to gain insight into whether students are satisfied with the newly developed serious game. More than 800 students participated in the online survey. Results were analysed using IBM SPSS. They show that students expect traditional educational material and tend to be less confident when facing entertaining material instead.